Penerapan Metode Active Learning Tipe Card Sort terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA Kelas VI SDN 8 Kalimbaung - Arsy Aulia Hamid; Nurlina; Nurul Magfirah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine students’ learning outcomes before and after the implementation of the Active Learning Card Sort method, as well as the improvement of science learning outcomes of sixth grade students at SDN 8 Kalimbaung. This study employed a quantitative approach with an experimental research type using a Pre-Experimental Design with a One Group Pretest-Posttest Design. The subjects of this study were all 23 sixth grade students. Data collection techniques were conducted through learning outcome tests in the form of pretest and posttest, observation, and documentation. The data were analyzed using descriptive statistics and the N-Gain test. The results showed that students’ learning outcomes before the implementation of the Active Learning Card Sort method were still categorized as low, with an average pretest score of 49.17 and all students had not achieved learning mastery. After the implementation of the Active Learning Card Sort method, the average posttest score increased to 85.74 and all students achieved learning mastery. The N-Gain test result obtained an average score of 0.7114, which was categorized as high. Therefore, it can be concluded that the implementation of the Active Learning Card Sort method was able to improve students’ learning outcomes in science subjects for sixth grade students at SDN 8 Kalimbaung.